Long-term effects of school spending: Evidence from exiting cohort size variation - Audun Langørgen; Sturla Andreas Løkken (Statistics Norway, Research Department, 2023)
This paper investigates the long-term effects of local government education spending on child outcomes, including income, educational attainment, and family formation in adulthood. We propose a novel identification strategy which exploits quasirandom variation in demographic trends when there is strong inertia in local government spending on compulsory schooling. Specifically, size of the exiting cohort that finishes compulsory schooling just before entry of the treated cohort is used as a source of exogenous variation. First, we show that exiting cohort size displays a significantly positive effect on per-pupil spending during school years of the treated cohort. Second, we argue that causal effects of school spending can be identified by utilizing exiting cohort size to instrument for school spending. In implementing this strategy, school spending is found to exhibit sizable and significant effects on income in adulthood for boys, with estimates that are relatively large for children from low- and middle-income families. By comparison, the effects of education spending are small and insignificant for girls.
Keywords: H42; H7; I2; J12; J62; 330; Education spending; School inputs; Compulsory schooling; Cohort size; Child outcomes; Local public finance